Effects of permafrost aggradation on peat properties as determined from a pan‐Arctic synthesis of plant macrofossils. Issue 1 (14th January 2016) - Treat, C. C.; Jones, M. C.; Camill, P.; Gallego‐Sala, A.; Garneau, M.; Harden, J. W.; Hugelius, G.; Klein, E. S.; Kokfelt, U.; Kuhry, P.; Loisel, J.; Mathijssen, P. J. H.; et al.
Abstract: Permafrost dynamics play an important role in high‐latitude peatland carbon balance and are key to understanding the future response of soil carbon stocks. Permafrost aggradation can control the magnitude of the carbon feedback in peatlands through effects on peat properties. We compiled peatland plant macrofossil records for the northern permafrost zone (515 cores from 280 sites) and classified samples by vegetation type and environmental class (fen, bog, tundra and boreal permafrost, and thawed permafrost). We examined differences in peat properties (bulk density, carbon (C), nitrogen (N) and organic matter content, and C/N ratio) and C accumulation rates among vegetation types and environmental classes. Consequences of permafrost aggradation differed between boreal and tundra biomes, including differences in vegetation composition, C/N ratios, and N content. The vegetation composition of tundra permafrost peatlands was similar to permafrost‐free fens, while boreal permafrost peatlands more closely resembled permafrost‐free bogs. Nitrogen content in boreal permafrost and thawed permafrost peatlands was significantly lower than in permafrost‐free bogs despite similar vegetation types (0.9% versus 1.5% N). Median long‐term C accumulation rates were higher in fens (23 g C m −2 yr −1 ) than in permafrost‐free bogs (18 g C m −2 yr −1 ) and were lowest in boreal permafrost peatlands (14 g C m −2 yr −1 ). The plant macrofossil record demonstrated transitions from fens to bogs to permafrost peatlands, bogs to fens, permafrost aggradation within fens, and permafrost thaw and reaggradation. Using data synthesis, we have identified predominant peatland successional pathways, changes in vegetation type, peat properties, and C accumulation rates associated with permafrost aggradation. Key Points: Permafrost aggradation history in peatlands was examined using plant macrofossil records Peat properties may reflect permafrost aggradation, especially nitrogen content Ecosystem succession in permafrost peatlands is highly dynamic and not unidirectional